What Difference Does a Methyl Group Make: Pentamethylbenzene?. Issue 17 (11th September 2014) - Mudge, Matthew; Ng, Boon K.; Onie, Catherine Jessica; Bhadbhade, Mohan; Mole, Richard A.; Rule, Kirrily C.; Stampfl, Anton P. J.; Stride, John A.
Abstract The crystal structure of pentamethylbenzene has been obtained for the first time with the use of synchrotron radiation, whilst the low‐energy spectrum of lattice dynamics, dominated by the methyl group torsions, was obtained using inelastic neutron scattering. The effect of symmetry lowering by the removal of a single methyl group relative to hexamethylbenzene has been investigated, including the role that this plays in the charge‐transfer characteristics of complexes formed with tetracyanoethylene.